Recent progress in performance improvement strategies for quantum dot sensitization methods: Challenges, achievements, and future prospects - Najm A.S.; Selvanathan V.; Aljuwaya T.M.; Sabri L.S.; Jamal M.S.; Abdullah Al-Zahrani A.; Holi A.M.; Jaber I.; Al Ghamdi A.; Amin M.T.; Sopian K.; Ismail R.A.; et al. (American Institute of Physics Inc., 2024)
In the recent past, there has been an increase in the use of semiconductor nanostructures that convert solar energy to electrical energy. This has encouraged the development of better and more efficient solar cells (SCs). Numerous investigations have been conducted into synthesizing novel semiconductor materials and tuning the electronic properties based on the shape, size, composition, and assembly of the quantum dots to improve hybrid assemblies. Recent studies that are determining the prospects of quantum dot SCs can form the basis for improving photovoltaic efficiency. Here, we have reviewed studies that investigated the sensitization methods for fabricating highly efficient SCs. We also discussed some examples that would help other researchers who want to sensitize quantum dot (QD) SCs. Thereafter, we analyzed the main and popular strategies that can be used for sensitizing the QD SCs within the limitations, advantages, and prospects of fabricating high-efficiency and stable QDs. During this work, we offered strong technical support and a theoretical basis for improving the industrial applications of QD. In addition, we provide a reference that can inspire other researchers who aim to improve the performance of SCs. 2023 Author(s).